Limitations of the circular economy concept in law and policy - Steenmans, Katrien; Lesniewska, Feja (Frontiers in Sustainability, 2023)
The circular economy (CE) concept has gained significant attention globally and nationally largely due to anticipated economic, environmental, and social benefits for sustainable development. As a result, laws and policies to advance CEs are increasingly being adopted nationally and regionally. In this perspective article we argue that a systematic approach to designing and implementing CE laws is necessary to cover the multi-level, multi-actor, and multi-sector dimensions of the CE concept. Such an approach should be built on a CE concept with clarified boundaries and scale to ensure it remains a meaningful concept and avoids perpetuating an unsustainable status quo. Moreover, a systematic approach should incorporate justice dimensions to deliver CEs that are fair, just, and inclusive. In the article we first identify five fundamental limitations to existing CE laws: (1) unclear boundaries and scale, (2) oversimplification of goals, (3) side-lining of justice dimensions, (4) reinforcement of the status quo, and (5) unintended consequences. Secondly, based on these limitations, we identify four directions for further research that can contribute to developing more effective CE laws. As there is no one-size-fits-all CE approach, any changes to existing laws and policies, or development of new ones, will require a wider evidence-base, from both the Global South and marginalized communities in the Global North, to reflect, inter alia, different practices, cultural relationships with material flows, and epistemological diversity.